THE ROLE OF COMMUNICATION IN THE FORMATION OF A PROFESSIONAL PEDAGOGICAL IMAGE (Eureka Journal of Education & Learning Technologies, 2026)
The professional image of a teacher is a multidimensional construct that reflects pedagogical competence, ethical standards, communicative behavior, and personal qualities demonstrated in interaction with students, colleagues, parents, and the wider educational community. In modern education, communication becomes not only a tool for transmitting knowledge but also a mechanism for building authority, trust, and cooperation. The article analyzes theoretical approaches to professional image formation and substantiates the decisive role of communication in shaping perceptions of the teacher’s personality and professionalism. Particular attention is given to communicative competence, verbal and nonverbal expressiveness, emotional intelligence, digital interaction, and conflict management.
Keywords: Professional image, pedagogical image, communication, communicative competence, teacher identity, pedagogical culture, emotional intelligence, interaction, professional ethics, digital communication